Molecular Characteristics of Autoimmune Pancreatitis - Jaster, Robert; Emmrich, Jorg (Current Pharmaceutical Design, 2006)
For many years, a pathological immune response has been implicated in the development of chronic pancreatitis. However, only in the last decade autoimmune pancreatitis (AIP) has been recognized as a distinct entity with typical histopathological and immunological findings. AIP is frequently associated with other autoimmune diseases, such as Sjogren's syndrome, sclerosing extra-hepatic cholangitis and retroperitoneal fibrosis. Although AIP is rare, improved diagnostics is of significant clinical interest because of the prompt response to steroid treatment. In this review, we describe the characteristic features of AIP and focus on the molecular pathogenesis of the disease.
Keywords: molecular pathogenesis